Oral Steroids or Watchful Waiting for Otitis Media with Effusion in Children: A Comparative Study of Hearing Outcomes - Muhammad Awais Samee, Bilal Zahid, Hassan Majid Bhatti, Syed Umair Iftikhar, Mohammad Qamar Nasir, Shahi Zeb, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Otitis media with effusion (OME) is a common acquired hearing loss in children and can impact on language and cognitive development in most cases. Even though most cases resolve on their own, the uses of oral steroids in enhancing the clearance of effusion speed and the final outcome of hearing is still debatable. Objective: To establish the efficacy of oral steroids as compared to watchful waiting in children with OME regarding hearing outcomes. Methods: The comparative study was done at the Department of Otolaryngology, Services Hospital Lahore, between June 2022 and January 2023. One hundred children with the age range of 3 to 12 years diagnosed with OME were recruited and divided into two groups. Group A was treated with oral prednisolone (1mg/kg/day, faded in 2 weeks), and Group B monitored. Baseline, 4 weeks, and 12 weeks Hearing thresholds were measured by pure-tone audiometry or age-adjusted tests. Tympanometry established the presence of effusion. The main outcome was improvement in hearing ( ≥10 dB gain or normalization) and secondary outcomes were resolution of effusion and adverse effects. The analysis of data was performed with the SPSS v26.0 based on chi-square, t-test, and repeated measures ANOVA, and p<0.05 was determined as significant. Results: At the baseline, the two groups were similar. Group A also experienced an increased hearing of 12.4 ± 4.3dB at 4 weeks as compared to 3.1 ± 2.6dB in Group B (p<0.001). By 12 weeks, the gains were still positive (14.617.2 dB vs. 8.914.8 dB; p=0.002). Group A had significantly more effusion resolution at 4 and 12 weeks (70 vs. 26 and 82 vs. 58, p=0.001 and 0.01, respectively). Side effects in steroid group were very mild and self limiting. Conclusion: The short-term effects of oral steroids are much more effective than the watchful waiting in hearing improvement and clearing the effusion. Nonetheless, since spontaneous remission takes place in most children, the watchful waiting is suitable in most simple cases whereas steroids can be used on a few children who may need quick recovery. Keywords: Otitis media with effusion, oral steroids, watchful pending, pediatric hearing loss, tympanometry.